2018
DOI: 10.1097/jsm.0000000000000457
|View full text |Cite
|
Sign up to set email alerts
|

Return to Driving After Hip Arthroscopy

Abstract: This study's findings suggest that patients may return to driving 2 weeks postoperatively from a right-sided hip arthroscopy procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(31 citation statements)
references
References 14 publications
1
30
0
Order By: Relevance
“…To the best of our knowledge, three studies have evaluated the time required to recover tness to drive after hip arthroscopy [2][3][4]. Two studies speci cally assessed patients undergoing arthroscopic FAI surgery using a simple driving simulator.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, three studies have evaluated the time required to recover tness to drive after hip arthroscopy [2][3][4]. Two studies speci cally assessed patients undergoing arthroscopic FAI surgery using a simple driving simulator.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Momaya et al analyzed the patients' braking performance using a realistic driving simulator similar to the simulator used in our study. They tested 14 patients who underwent various hip arthroscopy procedures on the right side and compared the braking parameters with those of 17 healthy volunteers [2]. The authors noticed signi cant improvements in the braking performance in the rst 2 weeks and concluded that return to driving at 2 weeks following right hip arthroscopy is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Momaya et al analyzed the patients' braking performance using a realistic driving simulator similar to the simulator used in our study. They tested 14 patients who underwent various hip arthroscopy procedures on the right side and compared the braking parameters with those of 17 healthy volunteers [2]. The authors noticed significant improvements in the braking performance in the first 2 weeks and concluded that return to driving at 2 weeks following right hip arthroscopy is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Hip arthroscopy is often indicated in young active adults, and the waiting time before resuming driving following the surgery is a common concern among the patients [ 1 , 2 ]. Pain, loss of proprioception, and discomfort from the surgical intervention may result in delayed responses of the affected leg, which could potentially lead to poor driving performance [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation